Effect of Not Receiving Measles Vaccines on Measles Illness in Songkhla Province - หริรัตนกุล อุทิศศักดิ์ (Journal of Health Science of Thailand, 2020)
Songkhla province has continuously reported measles outbreaks. The researcher therefore conducted this research with the objectives to assess the situation of measles outbreaks and to study the effect of not receiving measles vaccine on measles illness. It was conducted as a case control study by collecting patient history data from the patient report forms for diseases epidemiological surveillance. The sample were patients admitted to a hospital in Songkhla province between 2015 and 2019 by randomly selected from patients with completed data record. The sample size was 424 persons, 212 measles pateints as the cases and 212 patients with other respiratory diseases as the controls. Data were analyzed by using descriptive statistics, Chi-square test and test the measles vaccination effects on measles disease with Odds ratio (OR) using a statistics package software. The results showed that the the persons who had not been vaccinated with measles vaccine were 3.05 times more likely to have measles illness compared to those who were vaccinated with the measles vaccine (95%CI was between 1.97 and 4.74). The age group of measles vaccination by using the age range 0 to 8 months, which has not reached the age of measles vaccination as a reference group. Found that the age group without measles vaccination is likely to have measles 2.31 times more than those completely vaccinated group with a statistically significant of 95%CI between 1.31 and 4.08. And the single-dose measles vaccine was more likely to be the cases than measles vaccination complete was 1.89 times with a statistically significant 95%CI between 1.10 and 3.24. From the research results, it can be concluded that getting twice the measles vaccination according to the criteria can prevent measles up to as much as 2.31 times and getting just 1 measles vaccination can prevent as much as twice as measles. Therefore, there should be a campaign to get the measles vaccine according to the age range prescribed by the Ministry of Public Health, which is the first dose at the age of 9 months and the second dose at the age of 30 months or 2 and a half year olds.